2021
DOI: 10.1177/0272684x21996908
|View full text |Cite
|
Sign up to set email alerts
|

‘A Way to Know’ Your Stress: Acceptability and Meaning of Hair Sample Collection for Cortisol Analysis From African-American and Latina Women in a Digital Storytelling Study

Abstract: Obtaining biological samples for research purposes from members of marginalized communities demands careful social and ethical consideration. This paper aims to discuss how feasibility and acceptability translate into methodological and ethical considerations for collecting hair samples in a study comprised of young, pregnant Latinx and African-American women participating in a digital storytelling intervention (DST). Transcripts from two focus groups with Healthy Families home visitor staff (N =10) and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this study, we assessed the feasibility and acceptability of developing a DST intervention and explored a deeper understanding of Vietnamese American and Korean American mothers' rich personal experiences, meaning-making, attitudes, perceptions, and cultural views regarding their child HPV vaccination during three 2-day group-based DST workshops among Vietnamese American and Korean American immigrant mothers with children vaccinated against HPV. Although prior studies have examined the feasibility and acceptability of DST and its impact across diverse patient populations (cancer survivors, diabetic patients, patients experiencing stress) [29][30][31][32][33][34] and across different racial and ethnic groups (African American, Indigenous, and Latina women) previous to our own work, no DST studies with Vietnamese and Korean immigrants had been conducted, and no DST interventions had been designed to address the persistent HPV vaccination disparities among children of Vietnamese American and Korean American immigrant mothers. Gubrium et al [21] and Drenkard et al [35] discussed the challenges they faced in recruiting and retaining participants for workshops offered over consecutive days, given that disruptive life events and work schedules were limitations to minority participants' engagement in particular.…”
Section: Major Findingsmentioning
confidence: 99%
“…In this study, we assessed the feasibility and acceptability of developing a DST intervention and explored a deeper understanding of Vietnamese American and Korean American mothers' rich personal experiences, meaning-making, attitudes, perceptions, and cultural views regarding their child HPV vaccination during three 2-day group-based DST workshops among Vietnamese American and Korean American immigrant mothers with children vaccinated against HPV. Although prior studies have examined the feasibility and acceptability of DST and its impact across diverse patient populations (cancer survivors, diabetic patients, patients experiencing stress) [29][30][31][32][33][34] and across different racial and ethnic groups (African American, Indigenous, and Latina women) previous to our own work, no DST studies with Vietnamese and Korean immigrants had been conducted, and no DST interventions had been designed to address the persistent HPV vaccination disparities among children of Vietnamese American and Korean American immigrant mothers. Gubrium et al [21] and Drenkard et al [35] discussed the challenges they faced in recruiting and retaining participants for workshops offered over consecutive days, given that disruptive life events and work schedules were limitations to minority participants' engagement in particular.…”
Section: Major Findingsmentioning
confidence: 99%
“…In this study, we assessed the feasibility and acceptability of a digital storytelling (DST) intervention, and explored a deeper understanding of VA and KA mothers' rich personal experiences, meaning, attitudes, perceptions, and cultural views about their child HPV vaccination during three 2-day group-based DST workshops among VA and KA immigrant mothers with vaccinated children against HPV. Although prior studies have included African American, indigenous, and Latina women, examined the feasibility, acceptability of DST and its impact among cancer survivors, diabetic patients, or patients experiencing stress [29][30][31][32][33][34], there was a lack of DST related studies targeting Vietnamese and Korean immigrants and no DST has used as interventions to address the persistent HPV vaccination gap among VA and KA immigrant mothers' children. Our research is the rst one assessing the feasibly and acceptability of DST workshops among VA and KA mothers of HPV-vaccinated children.…”
Section: Discussionmentioning
confidence: 99%
“… 67 Strategies to promote sensitive hair collection procedures and maximise participant engagement include clear and respectful introductions and explanations of the reasoning behind hair collection, a comfortable and safe environment, parental involvement, flexible hair collection strategies/occasions and considerations of developmental and cultural preferences. 34 , 68 When discussing these issues with our YPAG, they did not raise major concerns about the EMA and indicated up to four prompts (EMA measurement instances) per day would be manageable, that having a wide window to respond, being told that they can miss some prompts if needed, having an offline data collection option and reminders to complete pending prompts would be helpful. They noted the challenges of responding during school time, both because of the school schedule and because they may not feel comfortable responding in the presence of peers for sensitive questions.…”
Section: The Mhim Strategymentioning
confidence: 99%
“…One study interviewed parents of youths with mental health conditions and identified trust, clarity and flexibility of the research process as key factors influencing participation 67 . Strategies to promote sensitive hair collection procedures and maximise participant engagement include clear and respectful introductions and explanations of the reasoning behind hair collection, a comfortable and safe environment, parental involvement, flexible hair collection strategies/occasions and considerations of developmental and cultural preferences 34,68 . When discussing these issues with our YPAG, they did not raise major concerns about the EMA and indicated up to four prompts (EMA measurement instances) per day would be manageable, that having a wide window to respond, being told that they can miss some prompts if needed, having an offline data collection option and reminders to complete pending prompts would be helpful.…”
Section: The Mhim Strategymentioning
confidence: 99%